TINGKAT PENYESUAIAN DIRI SISWA KELAS VII DI SMP NEGERI 11 KOTA BENGKULU - MINARSI - (Psikodidaktika, 2017)
This study was conducted in the city of Bengkulu SMP STATE 11 which aimed to obtain the level of adjustment class VII SMP Negeri 11 Bengkulu City. In this study, the analysis is self adjusting seventh grade students of SMPN 11 Bengkulu City. The method used the quantitative descriptive method. The study population as many as 159 students with a total sample of 76 students. Data collection techniques in this study using a questionnaire with data analysis technique used is descriptive analysis percentage. Once the data is collected and analyzed obtained results of the study that the rate adjustment seventh grade students of SMPN 11 Bengkulu city as a whole has a level adjustment is excellent only a small proportion who have moderate to good adjustment. Keywords: Level, Adjustment andStudents